1996
DOI: 10.1007/bf02598994
|View full text |Cite
|
Sign up to set email alerts
|

Sleep history is neglected diagnostic information

Abstract: Sleep problems are treatable causes of morbidity and mortality, but little is known about how often the history fundamental to diagnosis is obtained. We recorded the frequency of sleep histories during encounters with simulated patients by 20 experienced primary care practitioners, 23 uninstructed medical interns, and 22 interns who had previous instruction about sleep disorders. Sleep histories were uncommonly obtained by uninstructed physicians (0% of practitioners, 13% of interns), but trained interns more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 18 publications
1
56
0
2
Order By: Relevance
“…15 Aut hors no ted that physi ci ans did not rou ti nely scre en for sle ep di sor ders in ado les cents and sle ep prob lems we re un der di ag no sed. [16][17][18] In our study 40.1% of the par ti ci pants be li e ved that they had sle ep dis tur ban ces which was qu i te fre qu ent. A cross-sec ti o nal sur vey of 1535 scho ol chil dren (aged 5-18) which was con duc ted in New Or le ans, re por ted sle ep dis tur ban ce with a fre qu ency of 15.4% but the age gro up was yo un ger than our study.…”
Section: Discussionmentioning
confidence: 79%
“…15 Aut hors no ted that physi ci ans did not rou ti nely scre en for sle ep di sor ders in ado les cents and sle ep prob lems we re un der di ag no sed. [16][17][18] In our study 40.1% of the par ti ci pants be li e ved that they had sle ep dis tur ban ces which was qu i te fre qu ent. A cross-sec ti o nal sur vey of 1535 scho ol chil dren (aged 5-18) which was con duc ted in New Or le ans, re por ted sle ep dis tur ban ce with a fre qu ency of 15.4% but the age gro up was yo un ger than our study.…”
Section: Discussionmentioning
confidence: 79%
“…A history-and-physical sleep-audit coding sheet, designed to assess students' long-term knowledge retention and transfer of knowledge to patient care, was developed using validated screening history mnemonics such as BEARS 19 (bedtime issues, excessive daytime sleepiness, awakenings during the night, regularity and duration of sleep, snoring) and ISNORED 6 (insomnia, snoring and sleep quality, not breathing, older or obese, restorative or refreshing sleep, excessive day time sleepiness, drugs).…”
Section: Learning Outcome Instruments and Data Collectionmentioning
confidence: 99%
“…5 However, despite the prevalence of sleep disorders and the relationship of these disorders to underlying medical conditions, physician performance on sleep-related knowledge or skills assessments, from medical students through practicing primary care physicians, is poor at best. 6,7 As a result, many sleep disorders are undiagnosed in children and in adults. [8][9][10] Underdiagnosis of sleep disorders has been historically attributed to the limited inclusion of sleep medicine in medical school curricula.…”
mentioning
confidence: 99%
“…In one clinical study, residents who received didactic instruction about sleep disorders were found to ask about sleep more regularly in subsequent clinical encounters. 48 Finally, reimbursement issues may loom large among reasons why primary care providers do not routinely investigate insufficient sleep and sleep disorders. A sleep specialist can count on revenue from diagnostic procedures in the sleep laboratory to subsidize the time-intensive tasks of taking histories, counseling, education, or cognitive/behavioral therapy (for insomnia).…”
Section: What Are the Barriers To Screening For Insufficient Sleep/slmentioning
confidence: 99%